Implementation of Integrated Mismatch Negativity in Differentiating Children with Specific Language Impairment - Bardsley, Barry; Parker, David; Lockton, Elaine (Neuropediatrics, 2014)
Objective The study aimed to assess the use of Integrated Mismatch Negativity (MMNi) in differentiating children with specific language impairment (SLI) from a control group.Design Six conditions were created using a 1,000-Hz standard stimulus with three deviants of 1,020, 1,050, or 1,100 Hz and two interstimulus intervals of 400 and 200 ms. Recordings were processed offline using NeuroScan Edit (NeuroScan, Texas, United States). Four time analysis points were chosen and the magnitude of the integrated deviant was compared with the 100 standard subaverages. Mismatch negativity (MMN) presence was determined when 10 or less of the standard subaverages were less than the deviant subaverage magnitude.Study Participants A total of 18 children with SLI and 35 typical development children participated in the study.Results Pearson chi-square test demonstrated that the proportion of MMN presence in the SLI group was not significantly different from the control group and it did not vary with condition. Two-way between-group analysis of variance confirmed that using 1,000 Hz standard, 1,050 Hz deviant, and 400 ms interstimulus interval was significantly different from the other conditions.Conclusion MMNi does not serve as a tool for identifying children with SLI when using pure-tone stimuli. However, using different time analysis points with MMNi should be explored further, particularly with speech material.
Keywords: mismatch negativity; specific language impairment; identification